(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The botanical species of lettuce (Lactuca sativa L.) belongs to the family Astraceae. Its Lactuca sativa L. species is divided into the following subspecies: Lactuca sativa var. acephala - Oak leaf lettuce varieties; Lactuca sativa var. capitata - the Butterhead lettuce varieties of different shapes (buttery leaves have an oily layer); Lactuca sativa var. capitata – the Crisphead lettuce varieties of different shapes (Iceberg or Cabbage); Lactuca sativa var. romana – the Romaine lettuce varieties, or cos, long-round-leafed head lettuce, hemispherical forms are also found; Lactuca sativa var. Angustana (spargelsalad, wosun) - the Celtus lettuce varieties (stem lettuce). Lactuca sativa var. capitata, among other lettuces, is a crop of great importance in human health and agriculture. In the conditions of the Republic of Uzbekistan it has not been long since the beginning of the cultivation of head lettuce. The technologies in agriculture used in the cultivation of head lettuce in the country are not fully scientifically based today, and research in this area is one of urgent tasks and expedient.